45th Lithuanian National Physics Conference. October 25-27, 2023 Program and abstracts of presentations - Matijošius, Aidas; Maldžius, Robertas; Kuliešaitė, Miglė (Vilnius University Proceedings, 2023)
The publication presents the program of the Lithuanian National Physics Conference, traditionally held every two years, as well as abstracts of oral and poster presentations.
Keywords: Lithuanian national physics conference; conference program; abstracts of conference oral presentations; abstracts of conference poster presentations